2015
DOI: 10.1039/c5tb00202h
|View full text |Cite
|
Sign up to set email alerts
|

Tensile properties and in vitro degradation of P(TMC-co-LLA) elastomers

Abstract: The degradation mechanism of P(TMC-co-LLA) films was dependent on the LLA content and found to transition from heterogeneous to homogeneous bulk degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Indeed, if the amount of TMC in a copolymer of l -LA and TMC is ca . 16–21 mol %, it will slow down the heterogeneous bulk degradation process of PLLA, leading to a more homogenous decrease of the molar mass and longer retention of the physical properties of the material. , …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, if the amount of TMC in a copolymer of l -LA and TMC is ca . 16–21 mol %, it will slow down the heterogeneous bulk degradation process of PLLA, leading to a more homogenous decrease of the molar mass and longer retention of the physical properties of the material. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…16− 21 mol %, it will slow down the heterogeneous bulk degradation process of PLLA, leading to a more homogenous decrease of the molar mass and longer retention of the physical properties of the material. 42,47 Aliphatic polyesters usually present a bulk degradation behavior, and as a consequence of the statistical cleavage of the ester bonds along the macromolecules, the numbers of both carboxyl and hydroxyl chain-ends increase over time, while the number of reactive ester units decreases. Such a mechanism implies that the hydrolysis rate decreases over the experimental time, and therefore, an exponential decrease of the molar mass is observed.…”
Section: Assessment Of Hydrolytic Degradation Of Biomedical Polymers ...mentioning
confidence: 99%
“…These data demonstrate that the degradation profile of PTMC copolymers strongly depends on the chemical structure of the components, as well as backbone packing and crystallinity. Numerous other studies displayed an increase in the hydrolysis rate of PTMC copolymers when the ester content was raised in the composition, followed by a reduction of molar mass and tensile strength with time. …”
Section: Polycarbonate Degradationmentioning
confidence: 95%
“…The results indicated that the contact with water caused the decrease in mechanical properties. It is likely that PHBV absorbed water that acted as a plasticizer . Similar softening behaviors were observed in poly( d , l ‐lactide‐co‐glycolide) (PLGA) scaffolds, PLGA with calcium phosphate (Ca‐P) scaffolds, and PHBV/Ca‐P and poly( l ‐lactic acid) (PLLA)/ carbonated hydroxyapatite (cHA) scaffolds .…”
Section: Discussionmentioning
confidence: 68%